Anglo-American Law and Canon Law. : Canonical Roots of the Common Law Tradition. - Martínez-Torrón, Javier (Comparative Studies in Continental and Anglo-American Legal History - Band 18., 2013)
Hauptbeschreibung In the book at issue, the author endeavors to demonstrate a fact that has often been neglected by many Anglo-American legal historians: the Anglo-American legal tradition has more elements in common with Continental law than is frequently believed (Continent = European; continental law and doctrine: see also ""ius commune, ius utrumque""). The ""insularity"" of English law has never been complete. The learned laws, and particularly the canon law, have also played a very significant role in the historical evolution of English law. The formative process of the common law.